Economic analysis and optimal energy management models for microgrid systems: A case study in Taiwan - Chen, Yen-Haw; Lu, Su-Ying; Chang, Yung-Ruei; Lee, Ta-Tung; Hu, Ming-Che (Applied energy, 2013)
► An optimization model of energy supply in microgrid system is formulated. ► Optimal energy management strategies are determined. ► Sensitivity analyses of storage capacity and energy demand is performed. The purpose of this research is to perform economic analysis, formulate an optimization model, and determine optimal operating strategies for smart microgrid systems. Microgrid systems are electricity supply systems that integrate distributed renewable energy production for local demand. Microgrids are able to reduce transmission losses and improve utilization efficiency of electricity and heat. Further, greenhouse gas emissions are reduced by utilizing an efficient power generation microgrid system. This study presents an energy management model that is used to determine optimal operating strategies with maximum profit for a microgrid system in Taiwan. The smart microgrid system is equipped with energy storage devices, photovoltaic power, and wind power generation systems. Sensitivity analyses of investment in storage capacity and growth in electricity demand are conducted for the smart microgrid model. The results show that appropriate battery capacity should be determined on the basis of both battery efficiency and power supply.